Grammar and Punctuation - Ricky W. Telg (EDIS, 2015)
Any news story should be as free of grammar and punctuation errors as possible. Grammar is a system of rules that defines the use of the language. Most of the grammar and punctuation rules you have learned in school will be the same when using Associated Press Style, but there are some differences. This 4-page fact sheet covers some common grammatical and punctuation issues for journalists. Written by Ricky Telg, and published by the UF Department of Agricultural Education and Communication, January 2015. (Photo: iStock/Thinkstock)